Evaluasi Program Pemberdayaan Masyarakat (Prodamas) Plus : (Studi Kasus di Kelurahan Pakelan Kota Kediri) - Ferlita Salsabila Dwiyanti; Tauran Tauran; Tjitjik Rahaju; Firre An Suprapto (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Community empowerment is an effort to empower vulnerable community groups so they can become more independent and capable. The Kediri City Government has implemented the Prodamas Plus program, which in 2024 will focus on neighborhood-level initiatives in accordance with Kediri Mayor’s Regulation No. 28 of 2023. The Pakelan Subdistrict is carrying out this program with a focus on strengthening the “Kampung Keren” initiative due to its unique cultural characteristics. This study employs a qualitative case study approach using William N. Dunn’s evaluation model, which encompasses effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. Data were collected through observation, interviews, and documentation, then analyzed through the stages of data reduction, presentation, and verification. The results indicate that the Prodamas Plus program in Pakelan Subdistrict has been implemented fairly well, with tangible impact on infrastructure, the distribution of social assistance and a shift in residents’ roles toward becoming active agents of development, and the transformation of residents into active agents of development. However, the program still faces weaknesses, including delays in fund disbursement, suboptimal sustainable economic empowerment, a weak response to urgent needs, and an inflexible planning system. It is recommended that the focus of assistance be shifted toward productive activities accompanied by ongoing guidance, that disbursement mechanism be improved, and that the subdistrict design post-development maintenance plans and strengthen a personalized approach toward passive residents.